Word-Painting: Verbal-Visual Aesthetics in the Rossettis’ Poetry - Potîrniche, Cristina (Journal of Artistic Creation and Literary Research, 2025)
This paper analyzes the verbal-visual aesthetics in the poetry of Dante Gabriel and Christina Rossetti and how they achieved through different techniques a connection between words and images, in a way, creating a double-work of art that combines the visuality of paintings with the lyrical features of poetry. In order to explain that matter, first the Pre-Raphaelite Brotherhood and the innovations they presented in art in the nineteenth century will be introduced. Then, Dante Gabriel Rossetti’s Sonnets For Pictures are going to be interpreted to see how his use of pictorial and poetical symbolism is able to convey relevant meaning through the usage of symbols. To conclude this part, Dante shows how a poem could mirror an image through some of his ‘portrait poems’ and finally it is explained his particular ‘Theory of Mimesis’ which questions whether art is a realistic imitation of nature. In the part dedicated to Christina Rosseti, her religious background is considered, the way in which her devotional poetry includes many images in the form of biblical typology. Then, the analysis focuses on her most famous poem, “Goblin Market,” where the symbolic elements are ambivalent and could be interpreted in two different ways; either in religious or erotic terms. Finally, the paper concludes with a reflection upon the technique of ‘word-painting’ in the Rossettis’ poetry and how it was quite innovative for poetic profile as a whole.